STREET KIDS IN THE CHRISTIAN WORLD: A CASE OF MUTARE URBAN –ZIMBABWE - Kanjanda, Offard; Chiparange, Getrude Vongai (European Scientific Journal, ESJ, 2015)
A research was conducted in the City of Mutare to establish the plight of the street kids in an environment where Christianity is influencing every member of the community. The researchers were motivated to carry out this research because of the increase of street kids in both urban and rural settings of Zimbabwe. Street kids have developed a substructure society with its own values and norms which now seem to challenge the functional flavour of the traditional religion and culture in modern society. One would then wonder the kind of society that is emerging if nothing is done to restore harmony within the family institutions. The major objectives of the study were to encourage homeostatic balance within the family circles in order to create safe environments for the children. The research also aimed at encouraging Christians to create platforms for dialogue with the street kids so that they feel the warmth and acceptance by the society. The researchers employed the qualitative paradigm and adopted the case study as the design in order to gain in-depth study into the phenomena. The design also enabled the researchers to interact with the participants to understand how the street kids constructed their culture and behaviours to maintain and sustain their life. A sample size of 50 participants was selected using the stratified, purposive and convenience sampling techniques. The data were collected using the questionnaire with open-ended questions, direct observation and semistructured interviews. Ethical and legal issues were considered before, during and after collecting the data. The collected data were analysed descriptively. Theoretical frameworks such as the systemic, constructivism and functionalism were used in this research. The research revealed that harsh conditions such as loss of parents, abuse, neglect and poverty within the family institutions forced children to live in the streets. It also revealed that street kids abused drugs in order to activate their ego to gain courage for selfdefense. The research recommended that organisations that deal with street children should focus their programmes on family tracing and reunification since street children need care and proper upbringing in their natural family settings.